Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae) - Rheims, Cristina Anne (Zootaxa, 2016)
Neostasina gen. nov. is proposed to include the type species, Neostasina macleayi (Bryant, 1940) comb. nov., and four other described species: N. lucasi (Bryant, 1940) comb. nov. and N. saetosa (Bryant, 1948) comb. nov., transferred from Stasina Simon, 1877, N. bicolor (Banks, 1914) comb. nov., from Olios Walckenaer, 1837, and N. antiguensis (Bryant, 1923) comb. nov., from Pseudosparianthis Simon, 1887. Stasina portoricensis Petrunkevitch, 1930 and Olios darlingtoni Bryant, 1942 are considered junior synonyms of N. bicolor comb. nov. All species are redescribed and illustrated. Twenty-two new species are described, namely: N. baoruco sp. nov. (♀), N. bermudezi sp. nov. (♂, ♀) and N. cachote sp. nov. (♀) from the Dominican Republic, N. bryantae sp. nov. (♂, ♀), N. granpiedra sp. nov. (♂, ♀), N. iberia sp. nov. (♂, ♀), N. montegordo sp. nov. (♀), N. siempreverde sp. nov. (♂) and N. turquino sp. nov. (♀) from Cuba, N. croix sp. nov. (♂) from the Island of St. Croix and N. virginensis sp. nov. (♀) from the Island of St. John, both U.S. Virgin Islands, N. guanaboa sp. nov. (♂), N. gunboat sp. nov. (♂), N. jamaicana sp. nov. (♀), N. liguanea sp. nov. (♂, ♀), N. lucea sp. nov. (♀), N. mammee sp. nov. (♂, ♀), and N. maroon sp. nov. (♂, ♀) from Jamaica, N. ouali sp. nov. (♂, ♀) from Nevis Island, N. amalie sp. nov. (♂, ♀) from U.S. (St. John and St. Thomas Islands) and British Virgin Islands (Peter Island and Sandy Cay), and N. taino sp. nov. (♂, ♀) from Puerto Rico and Dominican Republic. An identification key and distribution maps are provided for all known species.